Umbilical Cord Tissue-Derived Cells as Therapeutic Agents - Olga Maslova; Miroslav Novak; Peter Kruzliak (Stem Cells International)
Although the characteristics of SC, including UC-derived cells, are a dramatically discussed issue, this review will focus particularly on some controversial issues regarding clinical utility of cells isolated from UC tissue. UC-derived cells have several advantages compared to other types and sources of stem cells. The impact of UC topography on cell characteristics is briefly discussed. The necessity to adapt existing methods of cell isolation and culturing to GMP conditions is mentioned, as well as possible cryopreservation of this material. Light is shed on some future perspectives for UC-derived cells.